2014
DOI: 10.1093/nar/gku1334
|View full text |Cite
|
Sign up to set email alerts
|

RECQL5 and BLM exhibit divergent functions in cells defective for the Fanconi anemia pathway

Abstract: Fanconi anemia (FA) patients exhibit bone marrow failure, developmental defects and cancer. The FA pathway maintains chromosomal stability in concert with replication fork maintenance and DNA double strand break (DSB) repair pathways including RAD51-mediated homologous recombination (HR). RAD51 is a recombinase that maintains replication forks and repairs DSBs, but also rearranges chromosomes. Two RecQ helicases, RECQL5 and Bloom syndrome mutated (BLM) suppress HR through nonredundant mechanisms. Here we test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 59 publications
2
35
0
Order By: Relevance
“…Intriguingly, co-depletion of BOD1L with another anti-recombinogenic helicase, RECQL5, failed to restore RAD51 foci formation and actually increased/accelerated fork degradation. This is in line with recent data demonstrating that the combined loss of FA proteins with RECQL5 is additive in terms of fork degradation and that BLM and RECQL5 have divergent functions in the absence of an intact FA pathway (Kim et al, 2015).…”
Section: Mechanisms For Bod1l In Stabilizing Rad51 On Damaged Chromatinsupporting
confidence: 92%
“…Intriguingly, co-depletion of BOD1L with another anti-recombinogenic helicase, RECQL5, failed to restore RAD51 foci formation and actually increased/accelerated fork degradation. This is in line with recent data demonstrating that the combined loss of FA proteins with RECQL5 is additive in terms of fork degradation and that BLM and RECQL5 have divergent functions in the absence of an intact FA pathway (Kim et al, 2015).…”
Section: Mechanisms For Bod1l In Stabilizing Rad51 On Damaged Chromatinsupporting
confidence: 92%
“…While limiting HR, RECQL5 counteracts the inhibitory effect of RAD51 on RAD52, thus promoting synthesis-dependent strand annealing (SDSA), which limits COs [56]. Deletion of RECQL5 in Fanconi anemia (FA) cells increases genomic instability, suggesting that RECQL5 in the HR-deficient context can induce compensatory repair mechanisms crucial for survival [57]. Another RecQ helicase, BLM, similarly inhibits the early recombinogenic step of displacing RAD51 from ssDNA in an ATP-dependent manner [58].…”
Section: Homologous Recombination Control: the Rad51 Hub In Homology-mentioning
confidence: 99%
“…[5][6][7][8][9][10][11] It seems that the DNA recombinase RAD51 is crucial for fork protection, and defects in RAD51-mediated fork protection underlie the uncontrolled fork resection observed in the absence of many components of the FA/HR pathway. The most wellcharacterized function of RAD51 is its ability to promote strand exchange during HR, by displacing the single-stranded DNA binding protein RPA to form helical nucleofilaments.…”
Section: Fork Protection Factorsmentioning
confidence: 99%
“…5,6 In addition to RAD51, the FA proteins FANCA, FANCB, FANCD2, PALB2 (FANCN), BRCA1 (FANCS) and BRCA2 (FANCD1) also suppress genomic instability upon replication fork stalling, by preventing the degradation of nascent DNA. 6,11,14 Since BRCA1, PALB2 and BRCA2 are required to load RAD51 onto ssDNA at stalled replication forks, it is natural to assume that their ability to protect replication forks from degradation is due to their role in this process. However, studies of a BRCA2 mutant that lacks a conserved C-terminal RAD51-binding site revealed that this region is essential for fork protection but dispensable for loading RAD51 onto DNA, and for HR.…”
Section: Fork Protection Factorsmentioning
confidence: 99%
See 1 more Smart Citation